PENGARUH DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA PT WOM FINANCE KEBUMEN - Hendrawardani, Blandina; Sukamto, Joko (Politeknik Dharma Patria Kebumen, 2019)
Companies in achieving organizational goals requires human resources with high performance. Sophistication teknoloogi owned by the company does not mean anything if they are not supported by adequate human resources. This study aimed to determine the effect of labor discipline on the performance of employees at PT WOM Finance Kebumen. The method used is descriptive quantitative method. The analytical method used is the Spearman rank correlation and coefficient of determination. The results showed that employee discipline and performance of employees at PT WOM Finance Kebumen are in either category in number 80,63% and 80%. The relationship between the variables of labor discipline with the performance of employees amounted to 0,833 at the 5% significance level that the degree is very strong relationship in a positive direction. The coefficient of determination showed 0.682 which means that the variable is explained by the variable performance of employees working discipline by 68.2% and the remaining 21.8% is explained by other factors beyond the study.